Growth on Oral Reading Fluency Measures as a Function of Special Education and Measurement Sufficiency. (January 2016) - Tindal, Gerald; Nese, Joseph F. T.; Stevens, Joseph J.; Alonzo, Julie
For 30 years, researchers have investigated oral reading fluency as a measure of growth in reading proficiency. Yet, little research has been done with these measures in the context of progress monitoring in Tier 2 systems. First, we document teachers' progress-monitoring decisions on type of passage (on-grade or off-grade) and how often to administer them. Then, we use a two-level hierarchical linear model to document the effects on both intercept and slope as a function of student special education status and measurement sufficiency. Across Grades 3 to 5, teachers diagnostically document student performance with different grade-level measures and also target a group of Tier 2 students to monitor early and systematically throughout the year. This latter group starts out much lower but has a significantly different slope than those for whom progress monitoring is more diagnostic and infrequent.